TYPES AND SELECTION OF TESTS FOR THE SPEED ABILITY OF SPRINTERS - Rade Stefanović; Dragana Ilić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Testing is a researching technique through which reliable data come. The instrument of researching technique is a test. The test is specified by the determinant of contents that possess researching contents and these are validity, reliability, objectiveness and discrimination. Pedagogic tests are carried out at field and there is a possibility for measuring. A scientific institution which deals with sport and sport medicine issues, can give great help in measuring, where by means of laboratory researches also gives a specific judgment on level of certain motor-functional abilities of sprinters. The testing is carried out among other things, in order to determine certain weaknesses with sprinters because of different level of their fast and efficient improvement are taken in consideration.